2021
DOI: 10.3390/jcm10061333
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perioperative Blood Transfusions on Microvascular Anastomoses

Abstract: Introduction: Perioperative transfusions are associated with complications of free flaps. The purpose of the present study was to find out whether there is a significant relationship between the risk of developing complications in vascular anastomoses and the history of transfusions. Methods: We studied 372 patients retrospectively with microsurgical reconstruction between 2009 and 2017 with regards to the number of red blood cell concentrates transfused. Complications were analyzed relative to flap loss and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…al, perioperative transfusions demonstrated a statistically significant association with microvascular anastomosis failure, however this was purely based on univariate analysis. 1 Studies have demonstrated a statistically significant incidence in re-operation rates for patients receiving greater than 3 units of PRBCs; however, this was only seen on univariate This article is protected by copyright. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…al, perioperative transfusions demonstrated a statistically significant association with microvascular anastomosis failure, however this was purely based on univariate analysis. 1 Studies have demonstrated a statistically significant incidence in re-operation rates for patients receiving greater than 3 units of PRBCs; however, this was only seen on univariate This article is protected by copyright. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…7 Overall, literature on the relationship between blood product transfusion and free flap reconstruction is limited and focuses on reconstructive procedures in the head/neck, or breast. 1,[8][9][10] These previous studies demonstrate mixed results, and the impact of transfusions on microanastomotic thrombosis, complication rates, and reoperation rates remains unclear. Furthermore, even though blood transfusions are commonly administered in trauma patients, their effect on LE free flap outcomes in the trauma population have not been studied before.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In a large database study of Korean adults, nearly 96% of liver transplant and 60% of kidney transplant recipients received at least one transfusion, most of which were plasma and/or platelets (37). Intraoperative RBC transfusions have been associated with postoperative thrombosis in general surgeries and in those involving free flaps (38, 39). This clinical observation is thought to be related to the changes in RBC deformability and accumulation of proinflammatory markers that occur during storage (40).…”
Section: Noncardiac Surgerymentioning
confidence: 99%